UV coating with imitation sandblasting effect, preparation method and application

By using specific formulas of UV coatings on electronic products to form a porous spider web structure coating, the problems of poor imitation sandblasting effect and rough feel in the prior art are solved, and a smooth feel and excellent wear resistance are achieved.

CN117004314BActive Publication Date: 2025-02-07HUNAN SONGJING ADVANCED SURFACE TREATMENT & FUNCTIONAL COATING RES INST CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311124117.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-01
Publication Date
2025-02-07
Estimated Expiration
2043-09-01

AI Technical Summary

Technical Problem

The prior art paints that are difficult to achieve imitation sandblasting effect in electronic products, and commonly used imitation sand particles will lead to rough feel, reduced wear resistance and increased weight.

Method used

Using a UV coating including polyurethane acrylate resin, active monomer, photoinitiator, leveling agent, matting agent, first solvent and second solvent, a specific formula ratio and preparation method can form a sandblasting effect. porous spider web structure coating.

Benefits of technology

It achieves a smooth feel, ultra-fine matte matte appearance and excellent covering and wear resistance on electronic products, while avoiding settlement and weight increase problems caused by imitation sand particles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117004314B_ABST
    Figure CN117004314B_ABST
Patent Text Reader

Abstract

The present invention relates to a UV coating with imitation sandblasting effect, a preparation method and application, which comprises the following components by weight: 15 to 30 parts of polyurethane acrylate resin, 25 to 40 parts of active monomer, 2 to 4 parts of photoinitiator, 0.1 to 3 parts of leveling agent, 45 to 75 parts of first solvent and 20 to 50 parts of second solvent. The UV coating with imitation sandblasting effect of the present invention does not need to add sand grain powder, glass powder or other imitation sand particles. Under the action of the solvent, the paint film can form a uniform and continuous porous spider web structure by itself, so that the paint film shows an ultra-fine matte matte appearance, like the texture of sandblasting, and also gives the paint film a smooth feel and excellent hiding and wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a UV coating with imitation sandblasting effect, a preparation method and application thereof, and belongs to the technical field of coatings. Background Art

[0002] With the rise of the electronic product consumer market, people are pursuing functional modules while also putting forward more demands on product appearance, feel, wear resistance, scratch resistance and other aspects.

[0003] The sandblasting process uses compressed air as the power to form a high-speed jet beam, which sprays the abrasive at high speed onto the surface of the workpiece to be processed, thereby increasing the roughness of the workpiece surface and forming an uneven surface (commonly known as a rough surface). The light on the workpiece surface is refracted, so it presents a matte surface with a strong texture and is not easy to stick to fingerprints, which is deeply favored by the market.

[0004] Usually, finer sand grain powder, glass powder or other imitation sand particles can be added to the coating formula to imitate the sandblasting effect. However, the sand grain powder has a large particle size and often protrudes from the surface of the paint film, shaped like mountains, resulting in a rough feel. Although the glass powder has a small particle size, it does not have a good imitation sandblasting texture. Fluff powder will reduce the wear resistance of the paint film. In addition, these imitation sand particles have a large specific gravity, which can easily cause the paint to sink to the bottom and clump, which is not conducive to long-term storage. When used in electronic products, they can easily increase the weight of the electronic products, which is not conducive to the lightweighting of electronic products such as mobile phones and tablets. Summary of the invention

[0005] In view of the deficiencies of the prior art, one of the purposes of the present invention is to provide a UV coating with a simulated sandblasting effect; a second purpose of the present invention is to provide a method for preparing the above-mentioned UV coating; a third purpose of the present invention is to provide the application of the above-mentioned coating in electronic products.

[0006] In order to solve the above technical problems, the technical solution of the present invention is as follows:

[0007] A UV coating with a simulated sandblasting effect comprises the following components, measured by mass: 15 to 30 parts of polyurethane acrylate resin, 25 to 40 parts of active monomers, 2 to 4 parts of photoinitiators, 0.1 to 3 parts of leveling agents, 2 to 10 parts of matting agents, 45 to 75 parts of first solvents and 20 to 50 parts of second solvents; wherein the first solvent comprises one or more of heptanol, octanol and nonanol; and the second solvent comprises one or more of alcohol compounds and alcohol ether compounds, and the boiling point of the second solvent is lower than that of the first solvent.

[0008] Furthermore, the following components are included, calculated by mass: 20 to 25 parts of polyurethane acrylate resin, 30 to 35 parts of active monomers, 2.5 to 3.5 parts of photoinitiators, 0.1 to 1 parts of leveling agents, 4 to 8 parts of matting agents, 50 to 70 parts of first solvents and 25 to 45 parts of second solvents.

[0009] Furthermore, the average molecular weight of the polyurethane acrylate resin is 1000-2000, preferably 1200-1800, and more preferably 1400-1600.

[0010] Furthermore, the polyurethane acrylate resin is one or more of difunctional aliphatic polyurethane acrylate, trifunctional aliphatic polyurethane acrylate, tetrafunctional aliphatic polyurethane acrylate, pentafunctional aliphatic polyurethane acrylate, and hexafunctional aliphatic polyurethane acrylate.

[0011] Optionally, the polyurethane acrylate resin adopts one or more of allnex EB8465 and Sartomer CN991.

[0012] Further, the active monomer includes at least one of a monofunctional UV monomer, a bifunctional UV monomer, and a multifunctional UV monomer;

[0013] Preferably, the active monomer is one of dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate;

[0014] Preferably, the viscosity of the active monomer is 7000-20000 cp, more preferably 10000-15000 cp.

[0015] Optionally, the active monomer is one or more of SR399LV, Changxing EM265, and SR399NS produced by Sartomer.

[0016] Furthermore, the photoinitiator is at least one of 1-hydroxy-cyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenylpropanone, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone, and (2,4,6-trimethylbenzoyl)diphenylphosphine oxide.

[0017] Optionally, the photoinitiator is at least one of BASF Irgacure-184, BASF Irgacure 2959, BASF Irgacure-1173, and Lucirin TPO.

[0018] Optionally, the leveling agent uses 9-dimensional APU-25.

[0019] Further, the first solvent is octanol, preferably secondary octanol;

[0020] Preferably, the second solvent is at least one of propylene glycol, ethanol, and propylene glycol methyl ether (CH3CHOHCH2OCH3).

[0021] Optionally, the matting agent includes one or more of silicon dioxide, wax powder, talcum powder, aluminum stearate, calcium stearate, and low molecular thermoplastic resin.

[0022] Optionally, the matting agent includes one or more of Grace SYLOID C803, Tosoh Nipsil E-1011, and Evonik EXP 8018-1.

[0023] The preparation method of the UV coating as described above comprises the following steps:

[0024] S1. Mix the photoinitiator, the leveling agent and the second solvent according to a ratio, and stir evenly to obtain a premixed solution;

[0025] S2, adding polyurethane acrylate resin, active monomer and matting agent to the premixed liquid, stirring at a rate of 800-1000 rpm for 20-30 min to obtain a mixed liquid;

[0026] S3, adding the first solvent into the mixed liquid, stirring evenly, and obtaining a finished UV coating product.

[0027] In this way, the photoinitiator, the leveling agent and the second solvent are first added, so that the photoinitiator can be fully dissolved and evenly mixed with the leveling agent and the second solvent; then the polyurethane acrylate resin, the active monomer and the matting agent are added to the premixed liquid and stirred, which helps to evenly disperse the matting agent, so as to finally obtain a uniform and stable UV coating product.

[0028] Furthermore, in S2, polyurethane acrylate resin, active monomer and matting agent are added to the premixed liquid, and stirred at a rate of 800 to 1000 rpm for 20 to 30 minutes to obtain a mixed liquid.

[0029] The application of the UV coating as described above or the UV coating prepared by the preparation method described above in electronic products comprises the following steps:

[0030] (1) Cleaning the target surface of the component of the electronic product to be coated with a UV coating to clean the target surface;

[0031] (2) applying the UV coating to the target surface to obtain a coating film with a thickness of 20-30 μm on the target surface;

[0032] (3) Bake the coated parts at 55-65°C for 10-20 minutes, then heat at 800-1200 mj / cm 2, 80~120mW / cm 2 UV curing under energy conditions to obtain a UV coating with a sandblasting effect on the surface of the component.

[0033] Optionally, the component is a housing of an electronic product.

[0034] Furthermore, the electronic products include 3C products. Furthermore, 3C products include computer, communication and consumer electronic products.

[0035] Furthermore, in step (2), the thickness of the coating film is 23-27 μm.

[0036] Optionally, the coating method is one or more of spraying, rolling, dipping, and electrophoretic coating.

[0037] Preferably, in step (3), the coated component is baked at 58-62°C for 12-18 minutes, and then heated at 900-1100 mj / cm 2 , 90~110mW / cm 2 UV curing under energy conditions.

[0038] After the UV coating of the present invention is applied, the first solvent such as the small molecule of octanol will follow the second solvent and evenly penetrate between the polymer molecular chains, weakening the attraction between the polymer molecular chains and increasing the distance between them. As the second solvent evaporates, the viscosity of the coating increases, and the polar groups on the polymer molecular chains form hydrogen bonds with the hydroxyl groups in the first solvent, which reduces the fluidity of the polymer molecules. After the first solvent is completely evaporated, pores are generated, so that the entire coating becomes a porous spider web structure (such as Figure 2 This structure will increase the scattering of light and reduce reflection, forming a matte effect, which looks like sandblasting (such as Figure 1 At the same time, the flatness of this porous spider web structure is much higher than that of the peak structure formed by filling with sand-like particles such as sand grain powder (such as Figure 3 ), so the hand feel will be smoother, no sedimentation will occur, and it is more convenient for long-term storage. In addition, a large amount of solvent is used in the UV coating of the present invention, and the solvent ratio is relatively high, and its cost can be significantly reduced compared with general coatings.

[0039] The UV coating with simulated sandblasting effect of the present invention does not need to add sand grain powder, glass powder or other simulated sand particles. Under the action of solvent, the paint film can form a uniform and continuous porous spider web structure by itself, so that the paint film shows an ultra-fine matte appearance, which is visually like the sandblasting texture, and at the same time gives the paint film a smooth feel and excellent hiding and wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1It is a digital photograph of the paint film formed by the UV coating of Example 1 of the present invention.

[0041] Figure 2 This is a 3D scanning modeling photo of the paint film formed in Example 1.

[0042] Figure 3 This is a 3D scanning modeling photo of the paint film formed in Example 5. DETAILED DESCRIPTION

[0043] The present invention will be described in detail below with reference to embodiments.

[0044] In each embodiment and comparative example, the leveling agent is Jiuwei APU-25; the matting agent is Tosoh Nipsil E-1011; the photoinitiator is at least one of BASF Irgacure-184, BASF Irgacure 2959, and Lucirin TPO. For details, see Table 13.

[0045] Example 1

[0046] The composition of the UV coating with the imitation sandblasting effect of the present embodiment is shown in Table 1.

[0047] Table 1 Formulation of UV coating imitating sandblasting effect of Example 1

[0048]

[0049]

[0050] The polyurethane acrylate resin is a trifunctional aliphatic polyurethane acrylate with an average molecular weight of 1400;

[0051] The active monomer is dipentaerythritol pentaacrylate, and its viscosity is 13600cp.

[0052] The preparation method of the above-mentioned imitation sandblasting UV coating is as follows:

[0053] S1, mixing the photoinitiator, the leveling agent and the solvent, stirring until dissolved, to obtain a premixed solution;

[0054] S2, adding polyurethane acrylate resin, active monomer and matting agent to the premixed solution of step S1, stirring at high speed for 25 minutes at a stirring rate of 900 rpm to obtain a mixed solution;

[0055] S3, adding solvent 1 to the mixed solution of step S2, stirring, and obtaining the coating.

[0056] Example 2

[0057] The composition of the UV coating with the imitation sandblasting effect of the present embodiment is shown in Table 2.

[0058] Table 2 Formulation of UV coating imitating sandblasting effect of Example 2

[0059]

[0060] The polyurethane acrylate resin is a trifunctional aliphatic polyurethane acrylate with an average molecular weight of 1400;

[0061] The active monomer is dipentaerythritol pentaacrylate, and its viscosity is 13600cp.

[0062] The preparation method of the above-mentioned imitation sandblasting UV coating is the same as that of Example 1.

[0063] Example 3

[0064] The composition of the UV coating for imitating sandblasting effect of the present embodiment is shown in Table 3.

[0065] Table 3: Formulation of UV coating for imitation sandblasting effect of Example 3

[0066]

[0067] The polyurethane acrylate resin is a trifunctional aliphatic polyurethane acrylate with an average molecular weight of 1400; the active monomer is dipentaerythritol pentaacrylate with a viscosity of 13600cp.

[0068] The preparation method of the above-mentioned imitation sandblasting UV coating is the same as that of Example 1.

[0069] Example 4

[0070] The composition of the UV coating for imitating sandblasting effect of the present embodiment is shown in Table 4.

[0071] Table 4: UV coating formula for imitation sandblasting effect of Example 4

[0072]

[0073]

[0074] The polyurethane acrylate resin is a trifunctional aliphatic polyurethane acrylate with an average molecular weight of 1400; the active monomer is dipentaerythritol pentaacrylate with a viscosity of 13600cp.

[0075] The preparation method of the above-mentioned imitation sandblasting UV coating is the same as that of Example 1.

[0076] Example 5

[0077] The composition of the UV coating for imitating sandblasting effect of the present embodiment is shown in Table 5.

[0078] Table 5: Formulation of UV coating for imitation sandblasting effect of Example 5

[0079]

[0080] The polyurethane acrylate resin is a trifunctional aliphatic polyurethane acrylate with an average molecular weight of 1400; the active monomer is dipentaerythritol pentaacrylate with a viscosity of 13600cp.

[0081] The preparation method of the above-mentioned imitation sandblasting UV coating is the same as that of Example 1.

[0082] Comparative Example 1

[0083] The composition of the UV coating of this comparative example is shown in Table 6.

[0084] Table 6 Formula of UV coating of comparative example 1

[0085]

[0086] The polyurethane acrylate resin is a trifunctional aliphatic polyurethane acrylate with an average molecular weight of 1400; the active monomer is dipentaerythritol pentaacrylate with a viscosity of 13600cp.

[0087] The preparation method of the above UV coating is the same as that of Example 1.

[0088] Comparative Example 2

[0089] The composition of the UV coating of this comparative example is shown in Table 7.

[0090] Table 7 Formula of UV coating of comparative example 2

[0091]

[0092]

[0093] The polyurethane acrylate resin is a trifunctional aliphatic polyurethane acrylate with an average molecular weight of 1400; the active monomer is dipentaerythritol pentaacrylate with a viscosity of 13600cp.

[0094] The preparation method of the above UV coating is the same as that of Example 1.

[0095] Comparative Example 3

[0096] The composition of the UV coating of this comparative example is shown in Table 8.

[0097] Table 8 Formula of UV coating of comparative example 3

[0098]

[0099] The polyurethane acrylate resin is a trifunctional aliphatic polyurethane acrylate with an average molecular weight of 1400; the active monomer is dipentaerythritol pentaacrylate with a viscosity of 13600cp.

[0100] The preparation method of the above UV coating is the same as that of Example 1.

[0101] Comparative Example 4

[0102] The composition of the UV coating of this comparative example is shown in Table 9.

[0103] Table 9 Formula of UV coating of comparative example 4

[0104]

[0105] The polyurethane acrylate resin is a trifunctional aliphatic polyurethane acrylate with an average molecular weight of 1400; the active monomer is dipentaerythritol pentaacrylate with a viscosity of 13600cp.

[0106] The preparation method of the above UV coating is the same as that of Example 1.

[0107] Comparative Example 5

[0108] The composition of the UV coating of this comparative example is shown in Table 10.

[0109] Table 10 UV coating formula of comparative example 5

[0110]

[0111]

[0112] The polyurethane acrylate resin is a trifunctional aliphatic polyurethane acrylate with an average molecular weight of 1400;

[0113] The active monomer is dipentaerythritol pentaacrylate, and its viscosity is 13600cp.

[0114] Preparation method of the above UV coating:

[0115] S1, mixing the photoinitiator, the leveling agent and the solvent, stirring until dissolved, to obtain a premixed solution;

[0116] S2. Add polyurethane acrylate resin, active monomer, matting agent and sand grain powder to the premixed liquid of step S1, and stir at high speed for 25 minutes at a stirring rate of 900 rpm to obtain the coating.

[0117] Comparative Example 6

[0118] The composition of the UV coating of this comparative example is shown in Table 11.

[0119] Table 11 Formula of UV coating of comparative example 6

[0120]

[0121]

[0122] The polyurethane acrylate resin is a trifunctional aliphatic polyurethane acrylate with an average molecular weight of 1400;

[0123] The active monomer is dipentaerythritol pentaacrylate, and its viscosity is 13600cp.

[0124] Preparation method of the above UV coating:

[0125] S1, mixing the photoinitiator, the leveling agent and the solvent, stirring until dissolved, to obtain a premixed solution;

[0126] S2. Add polyurethane acrylate resin, active monomer, matting agent and glass powder to the premixed liquid of step S1, and stir at high speed for 25 minutes at a stirring rate of 900 rpm to obtain the coating.

[0127] Comparative Example 7

[0128] The composition of the UV coating of this comparative example is shown in Table 12.

[0129] Table 12 Formula of UV coating of comparative example 7

[0130]

[0131] The polyurethane acrylate resin is a trifunctional aliphatic polyurethane acrylate with an average molecular weight of 1400;

[0132] The active monomer is dipentaerythritol pentaacrylate, and its viscosity is 13600cp.

[0133] Preparation method of the above UV coating:

[0134] S1, mixing the photoinitiator, the leveling agent and the solvent, stirring until dissolved, to obtain a premixed solution;

[0135] S2, adding polyurethane acrylate resin, active monomer, matting agent and fluff powder to the premixed liquid of step S1, stirring at high speed for 25 minutes at a stirring rate of 900 rpm, to obtain the coating.

[0136] The formula summary table of the coatings of Examples 1-5 and Comparative Examples 1-7 is shown in Table 13.

[0137] Table 13 Summary of formulations of coatings of Examples 1-5 and Comparative Examples 1-7

[0138]

[0139] In Table 13, “—” indicates that no addition was made.

[0140] The coatings of the above-mentioned Examples 1 to 5 and Comparative Examples 1 to 7 and the prepared UV coatings were subjected to performance tests. The test results are shown in Table 14.

[0141] The preparation method of the UV coating is as follows:

[0142] (1) Clean the target surface of the components (plastic parts) of electronic products to be coated with UV coating;

[0143] (2) applying the corresponding UV coating to the target surface to obtain a coating film with a thickness of 26 μm on the target surface;

[0144] (3) The coated parts were baked at 60°C for 15 minutes and then heated at 1000 mj / cm 2 , 100mW / cm 2 UV curing under energy conditions to obtain a UV coating with a sandblasting effect on the surface of the component.

[0145] Table 14 Performance test results of coatings and UV coatings of Examples 1 to 5 and Comparative Examples 1 to 7

[0146]

[0147]

[0148]

[0149] The imitation sandblasting effect paint films of the above-mentioned embodiments 1 to 5 have excellent properties. While presenting the visual effect of sandblasting texture, they can maintain a smooth feel, and can simultaneously enhance the user's visual, tactile and other aspects of the use experience. However, there is no sec-octanol in the coating formula of comparative example 1. Although it feels smooth, the paint film has no sandblasting texture. It can also be seen that although ethanol and sec-octanol are both alcohol compounds, ethanol cannot play the same role as sec-octanol. The sec-octanol content in the coating formula of comparative example 2 is too low, and the polymer molecular spacing cannot be expanded, resulting in a weak sandblasting texture. The sec-octanol content in the coating formula of comparative example 3 is too much, the polymer has poor film-forming properties, the sandblasting texture is poor, and the feel is dry. The solvent 2 in the coating formula of comparative example 4 is butyl acetate, the sandblasting texture of the coating is poor and the feel is dry, and the storage stability of the coating is also poor. The possible reason is that the miscibility of sec-octanol in ester solvents is low, resulting in poor film-forming properties and poor storage stability. In the coating of Comparative Example 5, although the sand grain powder can provide a good sandblasting texture to the paint film, it cannot provide a smooth hand feel and is easy to sink to the bottom and agglomerate. In the coating of Comparative Example 6, the glass powder provides a limited sandblasting texture to the paint film, and the hand feel is also unsatisfactory. In the coating of Comparative Example 7, although the fluff powder can provide a good hand feel, the sandblasting texture is insufficient, the wear resistance of the paint film is poor, and the appearance of the paint film is easy to be mottled.

[0150] Comparative Example 8

[0151] Example 1 was repeated, except that the average molecular weight of the polyurethane acrylate resin was 900.

[0152] Example 6

[0153] Example 1 was repeated, except that the average molecular weight of the polyurethane acrylate resin was 1,000.

[0154] Example 7

[0155] Example 1 was repeated, except that the average molecular weight of the polyurethane acrylate resin was 2,000.

[0156] Comparative Example 9

[0157] Example 1 was repeated, except that the average molecular weight of the polyurethane acrylate resin was 2100.

[0158] Comparative Example 10

[0159] Example 1 was repeated, except that the viscosity of the active monomer was 6000 cp.

[0160] Example 8

[0161] Example 1 was repeated, except that the viscosity of the active monomer was 7000 cp.

[0162] Example 9

[0163] Example 1 was repeated, except that the viscosity of the active monomer was 20,000 cp.

[0164] Comparative Example 11

[0165] Example 1 was repeated, except that the viscosity of the active monomer was 21000 cp.

[0166] Table 15 Performance test results of relevant coatings and UV coatings

[0167]

[0168]

[0169] It can be seen from Table 15 that by controlling the average molecular weight of the polyurethane acrylate resin and the viscosity of the active monomer within a specific range, the UV coating prepared with the relevant coating can exhibit excellent comprehensive performance. The UV coating has good adhesion, wear resistance, stability, sandblasting texture and smooth feel.

[0170] Comparative Example 12

[0171] Example 1 was repeated, except that the baking time was controlled to be 8 minutes during the preparation of the UV coating. The results showed that the paint film had a high gloss and was uneven, and the paint fell off in the boiling test. The possible reason was that the baking time was insufficient and too much 2-octanol remained in the paint film.

[0172] The contents explained in the above embodiments should be understood as these embodiments are only used to more clearly illustrate the present invention, and are not used to limit the scope of the present invention. After reading the present invention, various equivalent forms of modifications to the present invention by those skilled in the art all fall within the scope defined by the claims attached to this application.

Claims

1. A UV coating with imitation sandblasting effect, characterized in that: The invention comprises the following components in parts by mass: 15-30 parts of polyurethane acrylate resin, 25-40 parts of active monomer, 2-4 parts of photoinitiator, 0.1-3 parts of leveling agent, 2-10 parts of matting agent, 45-75 parts of first solvent and 20-50 parts of second solvent; wherein the first solvent comprises one or more of heptanol, octanol and nonanol; the second solvent is composed of one or more of alcohol compounds and alcohol ether compounds, and the boiling point of the second solvent is lower than that of the first solvent; the average molecular weight of the polyurethane acrylate resin is 1000-2000, and the polyurethane acrylate resin is one or more of difunctional aliphatic polyurethane acrylate, trifunctional aliphatic polyurethane acrylate, tetrafunctional aliphatic polyurethane acrylate, pentafunctional aliphatic polyurethane acrylate and hexafunctional aliphatic polyurethane acrylate; the viscosity of the active monomer is 7000-20000cp.

2. The UV coating according to claim 1, characterized in that: The composition comprises the following components in parts by mass: 20-25 parts of polyurethane acrylate resin, 30-35 parts of active monomer, 2.5-3.5 parts of photoinitiator, 0.1-1 parts of leveling agent, 4-8 parts of matting agent, 50-70 parts of first solvent and 25-45 parts of second solvent.

3. The UV coating according to claim 1, characterized in that: The average molecular weight of the polyurethane acrylate resin is 1200-1800.

4. The UV coating according to claim 3, characterized in that: The average molecular weight of the polyurethane acrylate resin is 1400-1600.

5. The UV coating according to claim 1, characterized in that: The active monomer includes at least one of a monofunctional UV monomer, a bifunctional UV monomer, and a multifunctional UV monomer.

6. The UV coating according to claim 5, characterized in that: The active monomer is one of dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate.

7. The UV coating according to claim 5, characterized in that: The viscosity of the active monomer is 10000-15000cp.

8. The UV coating according to any one of claims 1 to 7, characterized in that: The first solvent is octanol.

9. The UV coating according to claim 8, characterized in that: The first solvent is 2-octanol.

10. The UV coating according to claim 8, characterized in that: The second solvent is at least one of isopropanol, ethanol, and propylene glycol methyl ether.

11. The UV coating according to any one of claims 1 to 7, characterized in that: The matting agent includes one or more of silicon dioxide, wax powder, talcum powder, aluminum stearate, calcium stearate, and low-molecular thermoplastic resin.

12. The method for preparing a UV coating according to any one of claims 1 to 11, characterized in that: The following steps are involved: S1. Mix the photoinitiator, the leveling agent and the second solvent according to a ratio, and stir evenly to obtain a premixed solution; S2, adding polyurethane acrylate resin, active monomer and matting agent to the premixed liquid, stirring at a rate of 800-1000 rpm for 20-30 min to obtain a mixed liquid; S3, adding the first solvent into the mixed liquid, stirring evenly, and obtaining a finished UV coating product.

13. Application of the UV coating according to any one of claims 1 to 11 or the UV coating prepared by the preparation method according to claim 12 in electronic products, comprising the following steps: (1) Clean the target surface of the electronic product parts to be UV coated; (2) applying the UV coating to the target surface to obtain a coating film with a thickness of 20-30 μm on the target surface; (3) Bake the coated parts at 55-65°C for 10-20 minutes, then heat at 800-1200 mj / cm 2 , 80~120mW / cm 2 UV curing under energy conditions to obtain a UV coating with a sandblasting effect on the surface of the component.

14. The use according to claim 13, characterized in that The electronic products include 3C products.

15. The use according to claim 13, characterized in that: In step (3), the coated parts are baked at 58-62°C for 12-18 minutes, and then heated at 900-1100 mj / cm 2 , 90~110mW / cm 2 UV curing under energy conditions.

Citation Information

Patent Citations

  • UV curing coating, wear-resistant and antifouling coating layer and mobile phone protection film containing wear-resistant and antifouling coating layer

    CN104845521A

  • White board film matte UV coating and preparation method thereof

    CN111484798A